Factors influencing students' choice in pursuing diploma programme: a case in UTM Johor Bahru Campus / Anas Arshad, Norafika M Nor and Ahmad Nur Iman Othman - Arshad, Anas; M Nor, Norafika; Othman, Ahmad Nur Iman (2023)
This study investigates the factors that influence students' decisions when choosing the UTM diploma programme. The primary data was collected through a survey that was conducted on all active diploma students of the UTM Johor Bahru Campus. The responses of all 126 participating students were analysed using descriptive statistics such as frequencies, means, standard deviations and inferential analysis such as correlation, regression and reliability tests using the SPSS software. The findings indicate that there are three main factors that students consider in choosing a university: the university's reputation, the campus location and family influence. These findings have the potential to assist UTMSP ACE in addressing the pressing concern of the decrease in number of new intakes for the diploma programmes offered at the UTMJB Campus